PELAYANAN KESEHATAN TERHADAP PROGRAM JAMINAN SOSIAL DI RUMAH SAKIT AWAL BROS PANAM KOTA PEKANBARU TAHUN 2017 - Toya Muthia Septinabilla; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The National Health Insurance Program by the Health Social Security Organizing Agency is carried out as an effort to provide social protection in the health sector to participants to obtain health care and protection benefits in meeting basic health needs served by Health Facilities (First Level Health Facilities and Advanced Level Health Facilities). The participation of BPJS Health consists of Contribution Assistance Recipients (PBI) and Non-PBI Beneficiaries. However, one of the health facilities at the Awal Bros Hospital was identified as not providing good service, there were BPJS Health participants who did not feel the service benefits, such as inpatient rooms for class III KIS holders made difficult when using KIS, and participants' service information was not transparent BPJS Health. The formulation of the problem in this study, namely how and the inhibiting factors of health services to the Social Security Program at Pekanbaru Pekanbaru Bros Bros Hospital in 2017. The research method used was descriptive qualitative method with data collection instruments including interviews, study documentation related to the objectives research. The results of the study illustrate that the services carried out by the Pekanbaru Bros. Hospital Panam Hospital against the healthy Indonesian Cardholder community in 2017 have not run optimally, the health service benefits at the referral health facility (Initial Panam Pekanbaru Brochure) have not been felt by BPJS Health participants, where health has not been responsive and responsive in serving BPJS Health participants as well as referral administration tends to only be used for 1 (one) treatment so participants outside Pekanbaru City who need poor fees need additional fees for returning to medical treatment and receive referrals if routine medical treatment is needed against the same medical condition. Then information and complaints handling BPJS Kesehatan is more passive for BPJS Health participants with complaints that are online / information technology utilization rarely used by participants / economic community down as the main target of BPJS Health participants.Keywords: National Health Insur